Draft Annual Plan, 1994-95 Part I Planning Commission - Planning Commission (Planning Commission, 1994)
After the approval of the Approach Paper to the VIII Plan by the National Development Council in June 1991 the several economic and industrial policy reforms initiated by the Govt. of India would perforce call for a new orientation to the Five Year Plan. The priorities determined for the VIII Five Year Plan would be reflected in the Annual Plan 1994- 95. These are:— employment generation; containment of population growth; universalisation of elementary education, complete eradication of illiteracy among people of the age group of 15 to 35 years; (iv) eradication of scavenging and provision of safe drinking water, health and immunisation to all villages; (v) growth and diversification of agriculture to achieve self sufficiency in food and generation of surplus for export.
Planning Commission